A View of Zinc Electrowinnng Theory (The Australasian Institute of Mining and Metallurgy, 1977)
The main factors controlling the electro- winning of zinc from impure aqueous sulphate electrolytes are reviewed. Zinc, hydrogen and impurities are deposited at the cathode. The current effic- iency for zinc is increased by increasing zinc/ acid ratio and current density and by decreas- ing temperature; and may be unchanged, increased or decreased by the presence of impurity ions. A qualitative comparison of observed and predicted impurity effects is in reasonable agreement. Quantitative treatment of the effects of impurities and cell additives is not available. A tentative explanation of the time dependence of current efficiency in the presence of some impurities is provided. The forms in which impurities are deposited is substantially unknown. Impurities may be classified according to the extent of cathodic deposition. Procedures for control of cathodic deposition of impurities are outlined. The main anodic reactions are the forma- tion of oxygen, manganese dioxide and sulphuric acid. Minor reactions include the oxidation of lead, silver, cobalt and chloride. The site of the anodic reactions and the reactions generat- ing manganese dioxide are uncertain and may change with time of operation. The anode behaves crudely as an oxygen electrode with